2016
DOI: 10.1016/j.ijcard.2016.05.049
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of transcatheter aortic valve implantation via carotid artery access

Abstract: & Keywords BackgroundThe carotid artery is a novel access route for transcatheter aortic valve implantation (TAVI). This may represent a viable alternative in patients unsuitable for TAVI via traditional transfemoral access, up to 20%, as well as other access routes such as subclavian, transapical and aortic. This systematic review summarises the current evidence for its safety and feasibility. Methods A systematic review was conducted as per the Preferred Reporting Instructions forSystematic Reviews and Meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Gray and bibliography searching was done by reviewing the references of included studies and related review articles. The databases were searched with a combination of the key words: (transcatheter aortic valve replacement OR transcatheter aortic valve implantation OR TAVI OR TAVR) AND (transcarotid OR carotid artery OR transfemoral or transapical), as well as the following 'Medical Subject Headings' (MeSH) search terms derived from our previous review [12]: "TAVI", "TAVR", "PAVR", "aortic valve replacement", "aortic valve implantation", "aortic valve insertion", "aortic heart valve replacement", "aortic heart valve implantation", "aortic heart valve insertion". Last date of the search was 1st August 2017.…”
Section: Literature Search and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Gray and bibliography searching was done by reviewing the references of included studies and related review articles. The databases were searched with a combination of the key words: (transcatheter aortic valve replacement OR transcatheter aortic valve implantation OR TAVI OR TAVR) AND (transcarotid OR carotid artery OR transfemoral or transapical), as well as the following 'Medical Subject Headings' (MeSH) search terms derived from our previous review [12]: "TAVI", "TAVR", "PAVR", "aortic valve replacement", "aortic valve implantation", "aortic valve insertion", "aortic heart valve replacement", "aortic heart valve implantation", "aortic heart valve insertion". Last date of the search was 1st August 2017.…”
Section: Literature Search and Selection Criteriamentioning
confidence: 99%
“…Despite its invasiveness, it has shown favorable outcomes and lower complication rates. However, it is unsuitable for patients with severe respiratory pathology, as well as those with 'porcelain aorta' [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent meta-analyses and systematic reviews have suggested that the available data limit formal meta-analysis and, as such, they draw no firm conclusions regarding the safety and efficacy of this method. 31,32…”
Section: Trans-subclavian/transaxillarymentioning
confidence: 99%
“…In those with unfeasible access through one of the above strategies, bail鈥恛ut options include transcarotid and caval鈥揳ortic approaches. A systematic review on the transcarotid approach has shown comparable outcomes to other access routes, though sample size was small with heterogeneous endpoints . It can be undertaken under local anaesthesia or GA, though there was higher incidence of peri鈥恛perative strokes noted in the latter .…”
Section: Access Routesmentioning
confidence: 99%